Pengaruh Pemberian Jintan Hitam (Nigella Sativa) Terhadap Keterkendalian Glikemik Pada Pasien DIabetes Tipe 2 DI RUmah Sakit Umum Deli Serdang - Deby Maharani; Lita Septina Chaniago (Universitas Muhammadiyah Sumatera Utara, 2020)
Diabetes melitus type 2 is one of disease that frequently happen and the prevalensirate in a society tend to increase and this is an annual disease for the rest of our life. The purpose of this research is to find out the effect of glicemic in addition of black cumin oil to HbA1c (%) diabetes melitus type 2s content. This research is an experimental research with pretest post test control group design. The subject in this research is diabetes melitus patient type 2 in Deli Serdang Region Hospital based on the inclution and exclution criteria in October2018 with total of 22 person which grouped into standart and control group. Each group (n=11) had been checked for their HbA1c (%) at the beginning and at the end research for 8 weeks. In control groups patients had been given 500mg black cumin oil once a day as the addition of metformin. This research technique using purposive sampling and analyzing the data with paired sample t test with normality test using Shapiro-Wilk test. The result from this research that is we can see the HbA1c (%) average (last inspection) on patient with treatment (8,0889) is lower than the average HbA1c last inspection) on patient without treatment (8,4778). The result pairedsample t test P value = 0,017. There is a significant derivation with the diabetes melitus type 2 patients that had been treat with black cumin oil.Keywords: Black cumin oil, Diabetes, Poor glycemic control, Glycated hemoglobin (HbA1C)